TXNIP deficiency attenuates renal fibrosis by modulating mTORC1/TFEB-mediated autophagy in diabetic kidney disease - Yunxia Du; Ming Wu; Shan Song; Yawei Bian; Yonghong Shi (Renal Failure)
Thioredoxin-interacting protein (TXNIP) is an important regulatory protein for thioredoxin (TRX) that elicits the generation of reactive oxygen species (ROS) by inhibiting the redox function of TRX. Abundant evidence suggests that TXNIP is involved in the fibrotic process of diabetic kidney disease (DKD). However, the potential mechanism of TXNIP in DKD is not yet well understood. In this study, we found that TXNIP knockout suppressed renal fibrosis and activation of mammalian target of rapamycin complex 1 (mTORC1) and restored transcription factor EB (TFEB) and autophagy activation in diabetic kidneys. Simultaneously, TXNIP interference inhibited epithelial-to-mesenchymal transformation (EMT), collagen I and fibronectin expression, and mTORC1 activation, increased TFEB nuclear translocation, and promoted autophagy restoration in HK-2 cells exposed to high glucose (HG). Rapamycin, an inhibitor of mTORC1, increased TFEB nuclear translocation and autophagy in HK-2 cells under HG conditions. Moreover, the TFEB activators, curcumin analog C1 and trehalose, effectively restored HG-induced autophagy, and abrogated HG-induced EMT and collagen I and fibronectin expression in HK-2 cells. Taken together, these findings suggest that TXNIP deficiency ameliorates renal fibrosis by regulating mTORC1/TFEB-mediated autophagy in diabetic kidney diseases.